2016
DOI: 10.1007/s40195-016-0489-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Modeling of Friction Stir Processing-Based Crack Repairing in 2024 Aluminum Alloy

Abstract: A friction stir processing-based method was used to repair cracks in the 2024 aluminum alloy plates. The temperature field and plastic material flow pattern were analyzed on the basis of experimental and finite element simulation results. Microstructure and tensile properties of the repaired specimens were studied. The results showed that the entire crack repairing was a solid-phase process and plastic materials tended to flow toward the shoulder center and then resulted in the repairing of cracks. Meanwhile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Friction stir processing (FSP) is an effective method to fabricate Al alloys with ultrafine and equiaxed grains structure. It was found that this structure can promote the GB sliding in Al alloys [14][15][16][17][18][19], and these FSP samples always exhibit superplasticity [16,20,21]. Thus, FSP could be also used to improve the damping capacity of commercial Al alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Friction stir processing (FSP) is an effective method to fabricate Al alloys with ultrafine and equiaxed grains structure. It was found that this structure can promote the GB sliding in Al alloys [14][15][16][17][18][19], and these FSP samples always exhibit superplasticity [16,20,21]. Thus, FSP could be also used to improve the damping capacity of commercial Al alloys.…”
Section: Introductionmentioning
confidence: 99%
“…8b, and the averages of both the joint and NZ show the same trend with a peak value around HV135 at a PLD of 2.53 mm. This point (i.e., PLD 2.53 mm, HV135) implies adequate friction heating and a long dwell time at high temperature [23], which enables the intermetallics, such as Al 2 CuMg [24], to precipitate.…”
Section: Mechanical Properties Of the Jointsmentioning
confidence: 99%
“…Zhang et al [33] observed that increasing the rotational speed to more than 1400 rpm caused the formation of voids in the SZ. Kim et al [34], Ren et al [35], and Moussawi et al [36] studied the influence of rotational and traverse speeds on defects formation during FSP of aluminum alloys. In this regard, investigating the thermal aspects (peak temperature and thermal distribution) of FSP has attracted attention.…”
Section: Introductionmentioning
confidence: 99%